Quarkonia - Buchmuller, W. (Current physics--sources and comments, 1992)
The discovery of the two families of heavy-quark-antiquark bound states, the Ugr and PSgr quarkonium spectroscopies, has played a crucial role in unravelling the nature of strong interactions. The articles collected together in this volume are concerned with the connection between quarkonia and quantum chromodynamics. They deal with potential models, spin-dependent forces, next-to-leading order QCD corrections for decay widths and energy level differences, hadronic transitions and the quark-antiquark interaction in QCD, based on perturbation theory, lattice gauge theory and QCD sum rules. Finally, a brief guide is given to the existing literature on possible new quarkonium systems which have been conjectured in connection with gluonic degrees of freedom, and with expectations for new heavy particles with colour, such as the top quark and scalar quarks.